Blueprint: Lapintel Desk / Ag Benny Ag Jalil, Muhammad Arif Kamsani and Nur Adriana Mohd Borhan - Ag Jalil, Ag Benny; Kamsani, Muhammad Arif; Mohd Borhan, Nur Adriana (2018)
1.1 Business and product concept a) Our table is a practical which is suited to use in the office, home environment, for picnics, travel and etc. b) By implementing established technology into the desk, the product is combine with many different gadgets into one single desk. c) It's also healthier working when used in conjunction with a regular desk it enables the customers freeing from disorders such as backache and spondylitis caused by long hours sitting in the work place. 1.2 Target market and projection Our target market and projection are for students mainly and anybody in most level of ages can use of multipurpose table due to its flexibility and can help in making life more comfortable and more productive.